Changes in hospital human tissue oversight in the United States between 2005 and 2011: results of a follow‐up AABB survey. Issue 1 (15th May 2013) - Schlueter, Annette J.; Whitaker, Barbee I.; Gishta, Roksolana; Malasky, Jacquelyn; Josephson, Cassandra D.; ,
<x xml:space="preserve">Abstract</x> Background In 2005, The Joint Commission (TJC) implemented tissue storage and issuance standards for hospital oversight, which AABB assessed by survey. This follow‐up survey of AABB's membership, 6 years later, ascertained changes after TJC implementation of tissue standards. Study Design and Methods AABB's Biovigilance Tissue Working Group conducted a Web‐based survey, distributed to 1069 hospital institutional members in June 2011. Human tissue types used, departmental responsibilities, and views of AABB involvement were queried. Results Of the 336 (31%) total respondents, 84% use allogeneic and/or autologous human tissue. Sixty‐one percent have stored tissue on consignment. As in 2005, the department of surgery most often had responsibility for tissue use, followed by the blood bank or transfusion service (BBTS). Overall, the BBTS had a smaller role in oversight of autologous tissue acquisition in 2011 versus 2005, but no change in level of responsibility for storage or issue of tissues. Hospitals reported the BBTS and combined blood and tissue services (CBTS) added responsibilities for storing and monitoring eye tissue and heart valves (p < 0.05) since 2005. The BBTS/CBTS increased their degree of responsibility for reporting suspected postimplant infection and other adverse reactions for musculoskeletal allografts (p < 0.01), eye tissue (p < 0.005), and eye tissue recipients recall notification (p < 0.05). The BBTS/CBTS have more responsibility than any other department for stem cell and cord blood management. Conclusions In this survey, AABB institutional members reported that BBTS are more involved than previously in the regulatory aspects of human tissue oversight and remain involved in many operational aspects of hospital tissue management.